2014
DOI: 10.1016/s1995-7645(14)60225-x
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal activity of Persea americana Mill. against Aedes aegypti

Abstract: Both the hexane and ethanol extracts of P. americana showed promising potential as an alternative source of a more sustainable, non-toxic and environmentally friendly solution for the control of dengue vector, Ae. aegypti.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…These studies help improve our understanding of the dengue vectors, which could be useful in developing effective control strategies. Of the 21 articles in this category [52–72], six investigated dengue mosquito vector key breeding sites and potential interventions [52, 56–58, 60, 64], three described the response to or efficiency of vector control measures introduced in communities [54, 59, 61], five assessed the larvicidal activity of various agents against Aedes aegypti [55, 62, 65, 68, 70], three explored the characteristics and behavior of Ae . aegypti or Ae .…”
Section: Resultsmentioning
confidence: 99%
“…These studies help improve our understanding of the dengue vectors, which could be useful in developing effective control strategies. Of the 21 articles in this category [52–72], six investigated dengue mosquito vector key breeding sites and potential interventions [52, 56–58, 60, 64], three described the response to or efficiency of vector control measures introduced in communities [54, 59, 61], five assessed the larvicidal activity of various agents against Aedes aegypti [55, 62, 65, 68, 70], three explored the characteristics and behavior of Ae . aegypti or Ae .…”
Section: Resultsmentioning
confidence: 99%
“…Plant extracts of the Lauraceae family have been reported as effective natural pesticides against 3 th and 4 th instars larvae stages [46]. Larvicidal activity of L. puchury-major essential oil was not reported earlier.…”
Section: Bioassaysmentioning
confidence: 95%
“…aegypti mosquitoes [ 24 , 27 , 28 ]. Botanical insecticides can currently be synthesized from the extracts of leaves, seeds or fruits of many species of plants ( Figure 3 ) such as Apium graveolens , Persea americana , Cipadessa baccifera and Callistemon rigidus [ 29 , 30 , 31 , 32 ]. It is possible to isolate chemical components from the extracts and perform larvicidal bioassays or tests using adult mosquitoes according to the Guidelines for Laboratory and Field Testing of Mosquito Larvicides published by the WHO [ 33 , 34 , 35 ].…”
Section: Insecticides and Plant Extractsmentioning
confidence: 99%
“…There have been several studies that have identified natural compounds with insecticide or repellent characteristics [ 29 , 30 , 31 , 32 ]. In addition, Brazil encompasses significant biodiversity, and almost 19% of the world's flora grow in the country [ 38 ].…”
Section: Insecticides and Plant Extractsmentioning
confidence: 99%